Frugal Living Sebagai Solusi dalam Mengatasi Pinjaman Online Akibat Gaya Hidup Konsumtif - Mutmainah, Siti; Muhammad Ryan Romadhon (Yayasan Cendekia Gagayunan Indonesia, 2025)
The development of digital technology has given rise to the phenomenon of online loans that offer quick access with simple terms. However, this convenience is often abused to meet a consumptive lifestyle, triggering default problems. This study aims to analyze the role of frugal living (frugal lifestyle) in preventing dependence on online loans by reviewing its relevance in the perspective of Islamic economics. The research uses a qualitative descriptive approach through a literature review related to online lending practices, frugal living, and consumption ethics in Islam. The results show that frugal living, which emphasizes prioritizing needs, prudent financial management, and avoiding excessive spending, is able to suppress consumptive behavior and reduce dependence on online loans. This concept is in line with Islamic principles that prohibit excessive use of property. This study concludes that strengthening frugal living not only serves as a financial sustainability strategy, but is also relevant to Islamic ethics. The academic contribution of this research lies in the integration of the concept of frugal living with the perspective of Islamic economics, while practically recommending a financial literacy policy to increase individual resilience to online loans.